An overview of research and energy evolution for small hydropower in Europe - Manzano-Agugliaro, Francisco; Taher, Myriam; Zapata-Sierra, Antonio; Juaidi, Adel; Montoya, Francisco G. (Renewable & sustainable energy reviews, 2017)
Europe has a large tradition of Small Hydropower stations (SHP); these proliferate wherever there was an adequate supply of moving water and a need for electricity. As electricity demand grew many of these plants were abandoned. Today with the rising price of energy, SHP can be a solution to help rural electrification, furthermore SHPs do not consume the water that drives the turbines. The advantage of this technology is extremely robust and systems can last for 50 years or more with little maintenance. This paper summarizes an overview of SHP Hydropower in Europe. Hydropower on a small scale, or micro-hydro, is one of the most cost effective energy technologies to be considered for rural electrification in less developed countries. Europe is a market leader of SHP technology. Optimal turbine designs are available and new technical developments offer automated operation of SHP. The present role of SHP in Europe in the development of renewable energy sources is discussed through this paper. The main producers of SHP electricity in Europe are Italy, France, Spain, Germany and Sweden. On the other hand, 10 European countries are ranked based on the total numbers of SHPs: Germany (7,512), Italy (2,427), France (1,935), Sweden (1,901), Spain (1,047), Poland (722), Romania (274), Portugal (155) and UK (120). The research shows that there is a considerable scope for development and optimization of this technology. This opens new perspectives because it has a huge, as yet untapped potential in most areas of Europe and can make a significant contribution to future energy needs.